Crystals deposits in the anterior and posterior lens cortex in Bietti corneo-retinal dystrophy. (2nd November 2021) - Louati, Youssr; Vaclavik, Veronika; Moulin, Alexandre; Schorderet, Daniel; Munier, Francis L.; Viet Tran, Hoai
ABSTRACT: Background: Whereas crystals deposit in the retina, the cornea and limbus in Bietty corneo-retinal dystrophy (BCD) is now well established and documented, only two published cases report their findings in the lens and no cases deep in the lens cortex. Material and Methods: Four consecutive adult patients from three different unrelated families presenting lens crystals associated with advanced genetically confirmed BCD were enrolled with advanced disease and long follow up (>12 years). Demographics, visual acuity, slit lamp biomicroscopy, lens and posterior pole photography, optical coherence tomography (OCT), autofluorescence, and screening for CYP4V2 type of mutation were performed. The setting was Jules Gonin Eye Hospital, Switzerland, between 1.1 2013 and 1.11. 2019. Results: All patients were European women. The ages ranged from 40 to 81 years. Best Snellen visual acuity ranged from light perception to 1.0. All patients presented with limbus and retinal crystals deposit that disappeared over time and the development of severe chorioretinal atrophy. With long-term follow up, multiple crystal-like deposits appeared in the anterior, posterior lens capsule and cortex. All patients, but one, had homozygous or compound heterozygous mutations in CYP4V2 gene. Conclusions: To the best of our knowledge, there are no published cases of crystal deposits in the cortex of the lens of patients diagnosed with BCD associated with CYP4V2 gene mutation. This could be a feature of advanced BCD, and their presence in the lens cortex questions the hypothesis of floating deposits from posterior pole although their exact etiology remains to be determined.